Synthesis of symmetrical systems of discrete power functions - Білецький, А. Я.; Білецький, Є. А. (Proceedings of National Aviation University (archive), 2003)
The procedure of building up symmetrical matrixes, which form systems of basis digital power functions, is worked out and some peculiarities of using them for the spectral analysis of signals are discussed